Computational and experimental study of the cyclic voltammetry response of partially blocked electrodes. Part 1. Nonoverlapping, uniformly distributed blocking systems - Brookes, B; Davies, T; Fisher, A; Evans, R; Wilkins, S; Yunus, K; Wadhawan, J; Compton, R (2003)
The cyclic voltammetry response of partially blocked electrodes is modeled using finite difference simulations and a method presented for determining currents at electrode surfaces which have a well-defined geometric blocking pattern. Peak current and peak separation data are presented for six decades of scan rates, blocking coverage values between 0.1 and 0.9 and between the limits of reversible and irreversible electrochemistry. The validity of the simulation approach employed is verified by data obtained experimentally from purpose-built partially blocked gold film electrodes, with either a cubic or hexagonal geometric array of electroinactive disks uniformly distributed on the electrode surface. Comparison of theory with experiment suggests that the modeling of hexagonally distributed blocking systems is superior to that of the cubically arranged ones.